Effect of Boron Foliar Fertilizer and Mycoseed-Cookies on the Morphological and Seeds Production of Jack Bean (Canavalia ensiformis) - Armaji, Yone; Abdullah, Luki; Karti, Panca Dewi Manu Hara; Astuti, Dewi Apri; Nahrowi, Nahrowi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
This research identified the effects of foliar application of boron fertilization and arbuscular mycorrhiza in the form of cookies (Miko-SC) on the growth and seed production of Jack bean. Jack bean (Canavalia ensiformis) is a dual-purpose crop that produces seeds and green-biomass as a source of protein for human consumption and animal feed. Boron and Miko-SC significantly influences seed growth and development, and arbuscular mycorrhiza can enhance mineral uptake. This study employed four doses of boron foliar fertilizer (0, 23, 46, and 69 mg/l) and three diameters of Miko-SC (4, 5, and 6 cm). The highest values of plant height, stem diameter, and leaf size were observed in the combination of 46 mg/l boron and 5-cm Miko-SC. The highest number of leaves, pod weight, and grain weight were achieved at 23 mg/l boron combined with 6-cm Miko-SC. Conclusively, the optimal combination of boron and arbuscular mycorrhiza in the form of Miko-SC cookies significantly enhanced the growth of Jack bean, offering valuable insights into cultivation improvement as a forage and food crop.